Reconstructing past flow rates of southern component water masses using sedimentary 231Pa/230Th - Hickey, B (2010)
This thesis uses the paleoceancirculation proxy 231Pa/230Th, coupled with water mass tracers δ13C and εNd, to reconstruct circulation histories for southern source waters masses in the South Atlantic, in addition to North Atlantic Deep Water (NADW) far from its source, for the last ~25 kyrs. Downcore 231Pa/230Th records from a suite of cores along a depth transect in the Argentine Basin show distinct differences with depth, suggesting that 231Pa/230Th ratios in sediments are reflective of conditions in only the bottom most waters. This indicates the importance of consideration of changes in water mass distribution when interpreting 231Pa/230Th records. Opal and particle flux data from these cores show little correlation with 231Pa/230Th values meaning that changes in 231Pa/230Th cannot be explained by a local composition or particle flux effect and are instead likely to be reflecting changes in circulation. A core bathed by Antarctic Intermediate Water (AAIW) throughout the last 25 kyrs (GeoB 2107, 1045 m), has relatively high 231Pa/230Th values (0.075) during the Holocene and distincly lower values (0.055) at the LGM suggesting faster AAIW transport during the last glacial. At greater depths, 231Pa/230Th, δ13C and εNd data in core GeoB 2109 (2504 m) indicate a change in both circulation and water mass distribution on glacial-interglacial timescales, with moderate flow of Antarctic Bottom Water (AABW) at the LGM being replaced by more vigorous flow of NADW during the Holocene. On millenial timescales, 231Pa/230Th values in deep cores GeoB 2109 and GeoB 2112 (4010 m) indicate enhanced production of AABW during northern hemisphere stadials, when variations in 231Pa/230Th records are of opposite sign between hemispheres, supporting a possible bipolar seesaw relationship in deep water formation between hemispheres. These data indicate that the 231Pa/230Th proxy can be used to reconstruct past flow rates of multiple water masses in the Argentine Basin and provide evidence that southern source water masses play a dynamic counterpart to NADW formation on abrupt as well as glacial-interglacial timescales.